Levels of competitive behavior among athletes who have previously suffered sports injuries (case study of some clubs in the first regional division of the Batna and Constantine football leagues - senior category) - Hadji, Faycel; mouafek, saleh (sports creativity, 2025)
This study focused on investigating the impact of recurrent sports injuries on the competitive behavior of soccer players belonging to the first regional division of the Batna and Constantine leagues who had previously suffered sports injuries. The importance of this study lies in highlighting the psychological foundations of physical activity and raising awareness of the risks of injury in sports, as well as the need for injured players to undergo physical and psychological rehabilitation and the importance of modifying and guiding players' competitive behavior. The objectives of the study were to determine the level of competitive behavior among soccer players who had previously suffered sports injuries (belonging to the Batna and Constantine soccer leagues) and to identify the differences between them according to the variables of experience and playing position. As for the methodological procedures of the study, I chose the descriptive approach and selected a sample of 12 teams distributed equally between the two associations. I chose (Mohammed Hassan Alawi's competitive behavior scale) as the study tool after confirming its validity and reliability.